Mental heath is everybody´s business : mental health stigma in the workplace - Mariano, Raquel Agria de Almeida (2020)
Mental Health is a matter of utmost importance. Nonetheless, it is still intertwined with a culture of taboo and stigma. Many individuals with mental health conditions are sub-jected to unfair treatment as a result of stigmatized perceptions embedded in society. These stereotyped social constructs can impact their individuality coupled with undermining their ca-pabilities, namely in the realm of employment. Thus, the present research aimed to deconstruct these cultural structures in order to understand if stigma was present in the workplace, how it was being perpetuated and whether this environment could serve as a platform to challenge it. Therefore, through the dissemination and analysis of a questionnaire, insights were gathered regarding the matter. Findings suggested that, although stigma is indeed present in the work-place, it was less manifested than anticipated. Furthermore, these stigmatized views were mainly supported by perceptions of unaccountability and incapability, thus culminating in a culture of pity and sympathy. Contrarily, physical conditions were perceived with higher ac-countability which prompted negative reactions such as anger. Results also underlined an in-teraction between the culture of the organization and the personal level of stigma. Thus, when workplaces foster stigma-free practices, participants demonstrated decreased stigma towards individuals with mental health conditions. Therefore, as the present environment revealed to be a powerful platform to challenge stigma, it is recommended to all organizations to engage in such initiatives with the aim of fostering a society exempted from stigma.